Novel inhibitors of phosphorylation independent activity of GRK2 modulate cAMP signaling - Emiliana Echeverría; Sonia Ripoll; Lucas Fabián; Carina Shayo; Federico Monczor; Natalia C. Fernández (Wiley, 2022)
Abstract G protein‐coupled receptors kinase 2 (GRK2) plays a major role in receptor regulation and, as a consequence, in cell biology and physiology. GRK2‐mediated receptor desensitization is performed by its kinase domain, which exerts receptor phosphorylation promoting G protein uncoupling and the cessation of signaling, and by its RGS homology (RH) domain, able to interrupt G protein signaling. Since GRK2 activity is exacerbated in several pathologies, many efforts to develop inhibitors have been conducted. Most of them were directed toward GRK2 kinase activity and showed encouraging results on in vitro systems and animal models. Nevertheless, limitations including unspecific effects or pharmacokinetics issues prevented them from advancing to clinical trials. Surprisingly, even though the RH domain demonstrated the ability to desensitize GPCRs, this domain has been less explored. Herein, we show in vitro activity of a series of compounds that, by inhibiting GRK2 RH domain, increase receptor cAMP response, avoid GRK2 translocation to the plasma membrane, inhibit coimmunoprecipitation of GRK2 with Gαs subunit of heterotrimeric G protein, and prevent receptor desensitization. Also, we preliminarily evaluated candidates' ADMET properties and observed suitable lipophilicity and cytotoxicity. These novel inhibitors of phosphorylation‐independent actions of GRK2 might be useful in elucidating other RH domain roles and lay the foundation for the development of innovative pharmacologic therapy for diseases where GRK2 activity is exacerbated.